Relevance of Fama-French Three Factor Model to the Tehran Stock Exchange - Falavarjani, Majid Fazeli (2010)
This study applied the Fama French Three-Factor Model in the Tehran Stock Exchange (TSE). The purpose of this study is to find the explanatory power of the Three-Factor model in predicting return and risk on Tehran Stock Exchange (TSE).